How is recovery from low back pain measured? A systematic review of the literature - Kamper, Steven J. (Springer-Verlag, 2010)
Recovery is commonly used as an outcome measure in low back pain (LBP) research. There is, however, no accepted definition of what recovery involves or guidance as to how it should be measured. The objective of the study was designed to appraise the LBP literature from the last 10 years to review the methods used to measure recovery. The research design includes electronic searches of Medline, EMBASE, CINAHL, Cochrane database of clinical trials and PEDro from the beginning of 1999 to December 2008. All prospective studies of subjects with non-specific LBP that measured recovery as an outcome were included. The way in which recovery was measured was extracted and categorised according to the domain used to assess recovery. Eighty-two included studies used 66 different measures of recovery. Fifty-nine of the measures did not appear in more than one study. Seventeen measures used pain as a proxy for recovery, seven used disability or function and seventeen were based on a combination of two or more constructs. There were nine single-item recovery rating scales. Eleven studies used a global change scale that included an anchor of ‘completely recovered’. Three measures used return to work as the recovery criterion, two used time to insurance claim closure and six used physical performance. In conclusion, almost every study that measured recovery from LBP in the last 10 years did so differently. This lack of consistency makes interpretation and comparison of the LBP literature problematic. It is likely that the failure to use a standardised measure of recovery is due to the absence of an established definition, and highlights the need for such a definition in back pain research.